Extinction: a window into attentional competition. - Riddoch, M; Rappaport, S; Humphreys, G (2009)
Extinction is an example of how stimulus selection may be affected by an imbalance in competition for attentional selection. Patients with extinction are able to process stimuli in either hemispace, but only when presented in isolation. Following brain injury, stimuli will not be processed as efficiently in the damaged hemisphere and so may fail to be detected when other stimuli are competing for selection. In this review we discuss some of the factors that contribute to the recovery from extinction, and consider their implications for functional and neural theories of selection. Work shows that extinction can be modulated by multiple bottom-up factors including: low-level visual grouping (e.g., reflecting Gestalt properties in an array) and grouping based on higher level factors (such as the lexical identity of a stimulus or action relations between objects). Top-down factors (such as holding items in working memory) can also facilitate recovery from extinction. Furthermore, the competition for selection may also be modulated by the programming of action to a given location, consistent with pre-motor feedback to perceptual processes. While often discussed in terms of spatial biases, non-spatial extinction can also be demonstrated (dictated by the coherence of stimuli). In contrast to extinction, a phenomenon of anti-extinction has also been documented where patients are better at report when two items rather than single items are presented. Although superficially distinct, evidence indicates that grouping may be important in both cases, with temporal grouping being important in generating the anti-extinction effect. Overall, the work indicates that the disorder of extinction plays an important role in the understanding of attentional selection.